Catastrophic health expenditure among households with differently abled children and adolescents in Puducherry, India: a mixed-method study - Auroprem, Sona Priyanka; Kar, Sitanshu Sekhar; Devaraj, Loganathan; Thulasingam, Mahalakshmy (Frontiers in Public Health, 2025)
IntroductionHouseholds with disabled members are at greater risk of catastrophic health expenditure (CHE) due to their continual medical visits and treatments, the consequences of which force them into vicious cycles of impoverishment and distress financing. Additionally, they face various challenges in accessing healthcare, which compromises Universal Health Coverage (UHC). A significant gap exists in the cost of health expenditure for differently abled children in India.MethodsA mixed-methods study was conducted among 192 households, comprising 96 with differently abled children and 96 without. Quantitative data on health expenditures, insurance coverage, and utilization of disability benefits were collected through structured interviews. Catastrophic health expenditure was defined using the 40% of Capacity to Pay (CTP) threshold. Additionally, 10 IDIs were conducted among households with differently abled children to explore barriers and facilitators to healthcare access.ResultsApproximately 44.8% of the households experienced CHE at the 40% of CTP threshold. The most common type of disability reported was mental disability. Approximately 50% of the households did not have any insurance coverage, and only 44.8% were availing disability benefits for their child. As many as 77.1% of households experienced financial distress. A significant compensating variation was found. Barriers to health seeking included high medical expenses, poor accessibility, limited availability of specialized care, and lack of continuity in care. Facilitators such as good access to information, availability of healthcare facilities, and social support were also identified. Various recommendations to improve health-seeking were provided by parents.ConclusionThis study found a higher prevalence of CHE, distress financing, and numerous challenges for health-seeking among households with differently abled children, highlighting the need for prompt measures to address these issues.